Development of an Immunochromatography Assay to Detect Marburg Virus and Ravn Virus - Changula, Katendi; Kajihara, Masahiro; Muramatsu, Shino; Hiraoka, Koji; Yamaguchi, Toru; Yago, Yoko; Kato, Daisuke; Miyamoto, Hiroko; Mori-Kajihara, Akina; Shigeno, Asako; Yoshida, Reiko; Henderson, Corey W.; et al. (Viruses, 2023)
The recent outbreaks of Marburg virus disease (MVD) in Guinea, Ghana, Equatorial Guinea, and Tanzania, none of which had reported previous outbreaks, imply increasing risks of spillover of the causative viruses, Marburg virus (MARV) and Ravn virus (RAVV), from their natural host animals. These outbreaks have emphasized the need for the development of rapid diagnostic tests for this disease. Using monoclonal antibodies specific to the viral nucleoprotein, we developed an immunochromatography (IC) assay for the rapid diagnosis of MVD. The IC assay was found to be capable of detecting approximately 102−4 50% tissue culture infectious dose (TCID50)/test of MARV and RAVV in the infected culture supernatants. We further confirmed that the IC assay could detect the MARV and RAVV antigens in the serum samples from experimentally infected nonhuman primates. These results indicate that the IC assay to detect MARV can be a useful tool for the rapid point-of-care diagnosis of MVD.